Modern molecular photochemistry - Turro, Nicholas J. ([S.l.] : University Science Books, 1991)
During the last two decades the photochemistry of organic molecules has grown into an important and pervasive branch of organic chemistry. In "Modern Molecular Photochemistry", the author brings students up to date with the advances in this field - the development of the theory of photoreactions, the utilization of photoreactions in synthetic sequences, and the advancement of powerful laser techniques to study the mechanisms of photoreactions.
Keywords: photochemictry,molecular